Cholesterol crystal embolism in multiple organs after transarterial chemoembolization for hepatocellular carcinoma: An autopsy case report. Issue 39 (30th September 2022) - Yamashita, Junki; Nosaka, Takuto; Takahashi, Kazuto; Naito, Tatsushi; Ofuji, Kazuya; Matsuda, Hidetaka; Ohtani, Masahiro; Hiramatsu, Katsushi; Kobayashi, Motohiro; Nakamoto, Yasunari
Abstract : Rationale: Transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) rarely causes cholesterol crystal embolism (CCE). In our case, the histological findings suggested that the onset of CCE occurred at different time points in different organs. Patient concerns: A 72-year-old Japanese woman with HCC underwent TACE. After TACE, serum creatinine level and eosinophil count gradually increased. Three months later, she was admitted to our department with a fever and back pain. Diagnosis: Laboratory examinations showed sepsis with disseminated intravascular coagulation. She was treated with antimicrobial agents and anticoagulants, but died of multiple organ failure. Interventions: An autopsy was performed to examine the cause of multiple organ failure after 3 months of TACE. Outcomes: A mixture of both chronic phase emboli with intimal thickening and fibrosis and acute phase emboli with inflammatory cell infiltration were observed in the small intestine. Moreover, multiple intravascular cholesterol fissures were observed in the kidney, stomach, duodenum, colon, pancreas, and spleen, which were the vascular dominant organs of the celiac artery and superior mesenteric artery. These histological findings suggested that cholesterol crystals were continuously disseminated after TACE. Lessons: TACE for HCC may cause progressive CCE and damage in multiple organs. When progressive renal dysfunction, eosinophilia, or multiple organ dysfunction is observed after TACE, the CCE should be suspected.